Older truck drivers: How can we keep them in the workforce for as long as safely possible?. (January 2020) - Newnam, Sharon; Koppel, Sjaan; Molnar, Lisa J.; Zakrajsek, Jennifer S.; Eby, David W.; Blower, Daniel
Highlights: Explored factors associated with managing the safety of older truck drivers. Focus groups were conducted with fifteen safety managers in U.S. trucking companies. Identified challenges in addressing the needs of older truck drivers. Intervention must target the needs of this cohort and be realistic for the context. Abstract: There is convincing evidence to suggest that older truck drivers are a highly valued cohort in the transportation industry. Thus, ensuring the safety, health and wellbeing of this workforce should be a priority so that transportation industry employers can develop strategies to keep them driving for as long as they are safe on the road. As a first step in achieving this goal, the aim of this study was to better understand the key factors associated with managing the safety, health and wellbeing of older drivers in the trucking industry. Two focus groups with safety managers (n = 15) trucking companies in the United States were conducted to gain an understanding of the barriers and facilitators in planning and managing the safety of older truck drivers. Data were analyzed using thematic analysis and involved a broad categorisation of all meaningful data into four key areas (i.e., advantages, concerns, current strategies and challenges). Themes were subsequently identified within each of the four key areas. The results confirmed that older truck drivers are valued in the workforce for their work ethic and safety attitudes; however, there are multiple and interrelated factors influencing the safety management of older truck drivers. It was also found that there are few interventions that are targeted to the specific needs of older truck drivers and aligned to the challenges in managing the safety risks. Overall, the findings of this study support recommendations to address the barriers associated with managing the safety of older truck drivers.